Fundamentos e práticas do Colégio da Polícia Militar de Catalão: entre fardas, manuais e boletins - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The present dissertation results from a research whose objective was to understand the foundations and practices that support the educational process of the State College of the Military Police of Catalão - Polyvalent College. The object studied refers to a State College in Integral Time, whose management was transferred to the Military Police in the middle of 2016. The methodological route used was based on the case study and had as instruments for the production of the corpus the documentary research, the observation, the application of semi-structured questionnaires and the accomplishment of narrative-interviews. The narratives were analyzed by content analysis (BARDIN, 2009) and the set of all data submitted to triangulation (FLICK, 2009). In the first chapter, the understanding of pedagogy begins with the analysis of the foundations and manifest ideas in the guiding documents of the Polyvalent College which are the Pedagogical Model School of the School, the Novo Futuro Program, the Internal Regiment, the Political Pedagogical Project and the Plan of Action. In the second, we seek to understand the pedagogical by moving through the educational process in motion from narratives about categories delimited by the field of didactics such as curricular organization, planning, methods and resources and evaluation. In the third chapter the narratives on interpersonal relations give the keynote of the comprehensive exercise on the college. There is a dialogue with authors who discuss from the educational policies (BALL, 2011, 2013, LIBANNE, 2018, PERONI, 2012); (MIZUKAMI, 1987, LIBANEO, 2013, PÉRES GOMÉZ AND GIMENO SACRISTÁN, 1998, LIBÁNEO, 2013); of teacher training (CONTRERAS, 2013) and to a lesser extent authors who discuss power relations and domination as (Foucault, 1987; Weber, 2004). The results indicate that the pedagogical one suffers the influences of the liberal thought as base for the educational project that finds ballast in the political process of privatization of the education. This is reflected in its guiding texts (with ideals and principles aimed at the market) and the presence of the military that add to it the format marked by discipline and hierarchy (which, besides being accepted, are valued). In the bulge of this system emerges the reduction of the performance of teachers and educators in favor of an education beyond the walls of the school and future projects of adaptation to the system, which determines the reduction of the very function of education. It minimizes this interpretation to the observation that the college studied is a differentiated place that works full time, is valued by the community, has resources and partnerships, with organization and results-focused management exponent of neoliberal education thinking. In this sense it is an institution whose project does not fit with what critical educators and researchers expect as national public education, that is, that promotes social transformation or at least the reduction of inequalities.
Foundations and practices of the College of the Military Police of Catalão: between uniforms, manuals and bulletins
Keywords: Militarização da educação; Colégio cívico militar; Colégio da polícia militar; Fundamentos da educação; Práticas pedagógicas; Militarization of education; Military civic college; College of the military police; Fundamentals of education; Pedagogical practices; CIENCIAS HUMANAS::EDUCACAO